2017
DOI: 10.4274/jcrpe.3963
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin and Oxytocin Levels as Predictors of Metabolic Parameters in Obese Children

Abstract: Objective:Irisin and oxytocin can affect energy homeostasis and it has been suggested that they may play an important role in reducing obesity and diabetes. In this study, we aimed to determine the relationship between metabolic parameters (including irisin and oxytocin levels) and anthropometric parameters in obese children.Methods:Ninety obese children (mean age, 13.85±1.63 years) and 30 healthy controls (mean age, 14.32±1.58 years) were enrolled in this study. Anthropometric and laboratory parameters (gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 53 publications
(73 reference statements)
4
37
2
Order By: Relevance
“…The notion that elevated body fat impairs the glucoregulatory efficacy of oxytocin relates to the question of endogenous oxytocin release in metabolic disorders. While lower oxytocin concentrations were found in obese compared with normal‐weight adults and children, oxytocin levels have also been found to be proportional to body weight . In a large sample of men with metabolic syndrome, oxytocin concentrations were elevated compared with healthy controls, whereas the obese subjects of the present experiment displayed lower baseline oxytocin levels than their lean counterparts.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…The notion that elevated body fat impairs the glucoregulatory efficacy of oxytocin relates to the question of endogenous oxytocin release in metabolic disorders. While lower oxytocin concentrations were found in obese compared with normal‐weight adults and children, oxytocin levels have also been found to be proportional to body weight . In a large sample of men with metabolic syndrome, oxytocin concentrations were elevated compared with healthy controls, whereas the obese subjects of the present experiment displayed lower baseline oxytocin levels than their lean counterparts.…”
Section: Discussioncontrasting
confidence: 42%
“…In a large sample of men with metabolic syndrome, oxytocin concentrations were elevated compared with healthy controls, whereas the obese subjects of the present experiment displayed lower baseline oxytocin levels than their lean counterparts. Decreased oxytocin concentrations were reported in patients with metabolic syndrome or diabetes mellitus, suggesting a certain degree of oxytocin deficiency in diabetic patients . However, our preliminary finding of a positive relationship between HOMA‐IR and baseline oxytocin concentrations in the obese subjects argues against this assumption.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Therefore, it was not clear if the observed difference in oxytocin was due to obesity per se . In fact, subgroup analyses in the same study revealed that the children and adolescents with obesity and metabolic syndrome had significantly lower fasting oxytocin compared with those that had obesity without metabolic syndrome , supporting the notion that dysglycaemia may be a key factor in the lowering of plasma oxytocin concentrations in obesity.…”
Section: Alterations In the Oxytocin System In Obesity And Diabetesmentioning
confidence: 77%